Accelerated Reliability Demonstration Testing Design Based on Reliability Allocation of Environmental Stresses. (11th January 2017) - Li, Peng; Li, Chuanri; Dang, Wei
Abstract : The traditional reliability demonstration testing based on statistical method requires a large number of samples and long testing time, failing to satisfy the demand for short cycle and low cost. This paper proposes a new accelerated approach for determining reliability target of each environment stress, accelerated test profile, and comprehensive acceleration factor for multi‐failure mode product to conduct assembly level accelerated demonstration testing under multiple stresses and levels. By decomposing the product from four levels, namely function, structure, mechanism, and stress, the products' weaknesses can be identified. The main failure modes and sensitive environmental stresses are determined based on environmental profile and FMMEA. In this design, the reliability is apportioned to each actual environmental stress by AHP. And the SSI model is used to establish accelerated stress profile. The overall acceleration factor can be derived from the model of assembly level accelerated testing. Combined with a statistical plan, the accelerated reliability demonstration testing plan and test profile is built. A case example is presented to illustrate the effectiveness of the proposed approach. Copyright © 2017 John Wiley & Sons, Ltd.